Experimental study of carbon dioxide spectroscopic parameters around 2.0 µm region for combustion diagnostic applications. (November 2017) - Cai, Tingdong; Gao, Guangzhen; Wang, Minrui; Wang, Guishi; Liu, Ying; Gao, Xiaoming
Highlights: High temperature CO2 absorption spectra were recorded near 2.0 µm in the temperature range of 296–800 K. Line strengths for five selected strong CO2 lines were given at sample temperatures. Self-broadening coefficients and their temperature exponents were determined. Abstract: The high-resolution absorption spectra of carbon dioxide were measured at sample temperatures in the range of 296–800 K. The measurements were performed based on direct laser absorption spectroscopy using a tunable diode laser combined with a home-made heated static cell. Line strengths, self-broadening coefficients and their temperature dependences of five selected strong lines belonging to the 20012←00001 band of carbon dioxide near 2.0 µm were inferred from these measured spectra. To the best of our knowledge, this is the first study that measures the line parameters for the five selected strong CO2 lines at elevated temperature. The measured line strengths and self-broadening coefficients of these lines are compared with the available values listed in HITRAN/HITEMP database. The temperature dependence exponents of self-broadening coefficients are compared with theoretical calculations and values inferred from HITEMP2010. Agreements and discrepancies are discussed.